Hepatoprotective activity of ethanolic and aqueous extract of Turnera aphrodisiaca leaves against CCl4-induced liver injury in rats - Bathula, Naveen Kumar; Chowdhury, Bimalendu (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The botanical Latin name of the plant, Turnera aphrodisiaca, describes its ancient use as an aphrodisiac. Methods: The aim of the present study is to evaluate the protective effect of ethanolic and aqueous extract of Turnera aphrodisiaca leaves against carbon tetrachloride (CCl4)-induced liver damage in male Wistar rats. Results: Administration with ethanolic and aqueous extract of Turnera aphrodisiaca leaves (200 and 400 mg/kg) for 7 days significantly reduced the impact of CCl4 toxicity on the serum markers of liver damage, aspartate aminotransferase, alanine aminotransferase and alkaline phosphatase in a dose dependent matter. In addition, treatment of both the extracts resulted in markedly increased the levels of superoxide dismutase and catalase enzymes in rats. The histopathological studies in the liver of rats also supported that both extracts markedly reduced the toxicity of CCL4 and preserved the histoarchitecture of the liver tissue to near normal. Conclusion: Thus, the results suggest that ethanolic and aqueous extract of Turnera aphrodisiaca leaves acts as a potent hepatoprotective agent against CCl4 induced hepatotoxicity in rats.